Численно-полевой анализ силовых и энергетических процессов в турбогенераторе при несимметрии нагрузки - Милых, В.И.; Потоцкий, Д.В. (Технічна електродинаміка, 2017)
На основе численных расчетов вращающегося магнитного поля проведена оценка работы турбогенератора при несимметричной нагрузке в рамках ее стандартных ограничений. Проанализированы величины и временные функции силовых действий на стержни обмотки и части ферромагнитного сердечника статора, элек-тромагнитного момента и его пульсаций. Выявлено распределение мощности по фазным обмоткам статора и их коэффициенты мощности. Расчеты проведены на примере турбогенератора мощностью 35 МВт. Сопоставлены результаты при несимметричной и симметричной его нагрузках. На основі чисельних розрахунків магнітного поля, що обертається, проведено оцінку роботи турбогенератора при несиметричному навантаженні у рамках її стандартних обмежень. Проаналізовано величини і часові функції силових дій на стержні обмотки і частини феромагнітного осердя статора, електромагнітного моменту і його пульсацій. Виявлено розподіл потужності по фазних обмотках статора і їхні коефіцієнти потужності. Розрахунки виконано на прикладі турбогенератора потужністю 35 МВт. Зіставлено результати при несиметричному і симетричному його навантаженнях. Assessing the impact of load asymmetry of turbo-generator (TG) on the power and energy processes in it based on the numerical-field analysis within the constraints regulated by the standards. Methodology. Mathematical model of TG has been constructed on the method of symmetrical components of the three-phase current system. The unbalanced system of the currents is used for calculations of rotating magnetic fields. Thus the temporal functions of the electromagnetic and power quantities which are subjected to the harmonic analysis are obtained. Results. Calculations are conducted on a three-phase 35 MW TG during its work under autonomous unbalanced loading. The analysis of the temporal functions of the electromagnetic torque and the forces acting on the winding cores and the stator core ferromagnetic part has been executed. The distribution of power of their coefficients according to the phase windings was revealed.